ELECTRON-BEAM REDUCTION OF CUBIC Y-DOPED ZRO2(100) - A STUDY BY X-RAY PHOTOELECTRON-SPECTROSCOPY - Cotter, M; Egdell, R (1987)
Electron beam reduction of cubic Y(III)-doped ZrO2(100) has been studied by X-ray photoelectron spectroscopy. In the initial stages of irradiation with 2-keV electrons oxygen loss is accompanied by specific reduction of Zr(IV) to Zr(0) without concomitant reduction of Y(III). The cross section for oxygen desorption is estimated to be 3.9 × 10-20 cm2. Surface stoichiometry is restored by argon-ion bombardment. © 1987.